Thorium-232 fission induced by light charged particles up to 70 MeV - Métivier Vincent; Duchemin Charlotte; Guertin Arnaud; Michel Nathalie; Haddad Férid (EPJ Web of Conferences, 2017)
Studies have been devoted to the production of alpha emitters for medical application in collaboration with the GIP ARRONAX that possesses a high energy and high intensity multi-particle cyclotron. The productions of Ra-223, Ac-225 and U-230 have been investigated from the Th-232(p,x) and Th-232(d,x) reactions using the stacked-foils method and gamma spectrometry measurements. These reactions have led to the production of several fission products, including some with a medical interest like Mo-99, Cd-115g and I-131. This article presents cross section data of fission products obtained from these undedicated experiments. These data have been also compared with the TALYS code results.